Significance of exome sequencing for diagnosis of epilepsy in children - T. V. Kozhanova; S. S. Zhilina; T. I. Meshheryakova; K. V. Osipova; S. O. Ayvazyan; A. G. Prityko (Эпилепсия и пароксизмальные состояния)
Introduction. Epilepsy is a neurological disorder characterized by periodic seizure attacks. Around 70–80% of epilepsy cases have a hereditary component.Aim: to identify the genetic factors of pharmacoresistant epilepsy in children.Materials and methods. Fifty two patients with epilepsy and psychomotor / speech retardation were examined. We used the next generation sequencing (NGS) technique, which is the targeted exome sequencing, the “Hereditary epilepsy” panel of genes, and the whole exome sequencing assay.Results. Mutations were detected in 30 (57.7%) patients, while 22 patients had no mutations. In the latter cases, either epilepsy was of non-hereditary nature or the tested nucleotide sequence was located in the non-coding part of the gene (intron); in addition, a chromosomal rearrangement could be involved.Conclusion. The obtained data illustrate a diagnostic significance of the whole exome sequencing and encourage the interaction between an epileptologist and a geneticist in the diagnostic procedure. Identification of the genetic base of the disease is of great importance for genetic counseling and for selecting an antiepileptic therapy in this group of patients.The authors declare about the absence of conflict of interest with respect to this publication. Authors contributed equally to this article.